Bi2WO6 Nanocrystals with High Photocatalytic Activities under Visible Light - Shang, Meng; Wang, Wenzhong; Sun, Songmei; Zhou, Lin; Zhang, Ling (Journal of physical chemistry. C, 2008)
Visible-light-induced photocatalyst Bi2WO6 with the size of ca. 30 nm has been synthesized via a facile template-free hydrothermal method. The effects of the pH values of the precursor suspensions and hydrothermal time on the photocatalytic activities of the Bi2WO6 nanoplates have been investigated in detail. The photocatalytic activity of as-prepared Bi2WO6 was about 8−10 times higher than that of the product prepared by solid-state reaction, which was evaluated by the degradation of RhB dye in water under visible light irradiation. Even under the illumination of a compact fluorescent lamp, the nanosized Bi2WO6 also exhibited high photocatalytic activity.